rboAnalyzer: A Software to Improve Characterization of Non-coding RNAs From Sequence Database Search Output - Schwarz, Marek; Vohradský, Jiří; Modrák, Martin; Pánek, Josef (Frontiers in Genetics, 2020)
Searching for similar sequences in a database via BLAST or a similar tool is one of the most common bioinformatics tasks applied in general, and to non-coding RNAs in particular. However, the results of the search might be difficult to interpret due to presence of partial matches to database subject sequences. Here, we present rboAnalyzer – a tool that helps with interpreting sequence search result by 1) extending partial matches into plausible full-length subject sequences, 2) predicting homology of RNAs represented by full-length subject sequences to the query RNA, 3) pooling information across homologous RNAs found in the search results and public databases such as Rfam to predict more reliable secondary structures for all matches and 4) contextualizing the matches by providing the prediction results and other relevant information in a rich graphical output. Using predicted full-length matches improves secondary structure prediction and makes rboAnalyzer robust with regards to iden-tification of homology. The output of the tool should help the user to reliably characterize non-coding RNAs. The usefulness of the rboAnalyzer output and also the ability of rboAna-lyzer to correctly extend partial matches to full-length matches are both demonstrated here using known homologous RNAs. To allow the user to use custom databases and search options, rboAnalyzer accepts any search results as a text file in the BLAST format. The main output is an interactive HTML page displaying the computed characteristics and other context for the matches. The output can also be exported in an appropriate sequence and/or secondary structure formats.